Pengaruh Pengawetan dengan Metode Penggaraman dan Pembekuan Terhadap Kualitas Ikan Bandeng (Chanos chanos) - Dewi Kresnasari (Scientific Timeline, 2021)
Fish is a source of animal protein that all levels of society can accept. This protein's benefits will be obtained optimally if the fish's quality remains in the excellent category. A preservation method such as freezing and salting is needed to maintain the excellent quality of fish. This study aimed to determine the effectiveness of preservation by freezing and salting on milkfish (C.chanos) quality. The research implementation time was 15-17 July 2019. Some of the treatments used were milkfish (C.chanos) without salting (control), 20% salting, 30% salting, 40% salting, and just freezing. An organoleptic test with a scoring method was conducted to determine the quality of the fish. Number 1 was the lowest value, while number 9 was the highest. The scoring results were then analyzed descriptively. The observations showed that the freezing method gives the best results, following the 40% salting method, 30%, and 20% salting. The lowest results were obtained in control fish (without treatment).